T2 measurement and quantification of cerebral white and gray matter aspartate concentrations in vivo at 3T: a MEGA‐PRESS study. Issue 1 (12th March 2019) - Menshchikov, Petr; Manzhurtsev, Andrei; Ublinskiy, Maxim; Akhadov, Tolib; Semenova, Natalia
Abstract : Purpose: To measure the transverse relaxation rate (T2 ) of aspartate (Asp) from Asp‐edited MEGA‐PRESS spectra and use the measured T2 values to estimate the Asp concentrations in gray matter (GM)‐ and white matter (WM)‐dominant brain regions. Methods: Since Asp‐edited MEGA‐PRESS spectra contain non‐overlapped Asp signals, TE‐dependence arising from J‐evolution can be considered using phantom MEGA‐PRESS spectra acquired with the same parameters as in vivo spectra. Four TE values (90, 115, 140, and 150 ms) were selected from numeric analyses for effective detection of the edited Asp multiplet at ~2.71 ppm. The T2 relaxation time was measured in the anterior cingulate cortex (ACC) of 16 healthy volunteers. Absolute cerebral Asp concentrations were measured with Asp‐edited MEGA‐PRESS in the ACC and left centrum semiovale (CS) of 44 healthy volunteers at TEs of 90, 115, 140, and 150 ms. Results: The in vivo and phantom T2 values of the edited Asp signals were 165 ± 37 ms and 313 ± 27 ms, respectively. The cortical GM concentration quantified was significantly greater than the WM concentration (2.80 ± 0.31 mM vs. 1.01 ± 0.18 mM). Conclusion: MEGA‐PRESS is the most common editing method used for low‐concentration metabolites detection. Estimation of the absolute Asp concentrations has potential in many research applications, such as studying the processes underlying the reduction of N‐acetyl aspartate as well as studying mitochondrial diseases etc. The T2 measurement method described has been successfully applied for edited Asp signals. This method can also be used for other strongly J‐coupled signals.